L’estetica di Romano Guardini (III). La maturità del 1938 - Ascencio LC, Juan G. (Alpha Omega, 2013)
This article –the third of a series- studies the developments in Romano Guardini’s aesthetic thought around 1938, thus reaching the point of his mature thought. Special attention is given to the relation between the well known 1947 conference “The work of art” and the synthesis obtained in 1938. A series of fourteen conceptual elements is established and analyzed in order to bring to light Guardini’s own aesthetic theory.